SUBRETINAL FIBROSIS AFTER ANTIVASCULAR ENDOTHELIAL GROWTH FACTOR THERAPY IN EYES WITH MYOPIC CHOROIDAL NEOVASCULARIZATION. Issue 11 (November 2016) - Ahn, Seong Joon; Park, Kyu Hyung; Woo, Se Joon
Abstract : Purpose: To assess the incidence and risk factors of subretinal fibrosis and their impact on visual outcome in eyes with myopic CNV. Methods: Medical records of 72 eyes treated with antivascular endothelial growth factor (anti-VEGF) therapy in a pro re nata regimen for myopic CNV that followed up for more than 1 year were retrospectively reviewed. The presence of subretinal fibrosis after anti-VEGF therapy was determined using both fundus photographs and optical coherence tomography. The incidence and risk factors of subretinal fibrosis were evaluated, and best-corrected visual acuity was compared between the eyes with and without subretinal fibrosis. Results: The incidences of subretinal fibrosis during the 1-year and whole follow-up period were 31.9% and 36.1%, respectively. Occurrence of subretinal fibrosis was associated with frequent CNV recurrence ( P = 0.005) and poor baseline best-corrected visual acuity ( P = 0.044) in a Cox proportional hazard model. Anatomically, the eyes with subretinal fibrosis showed more frequent progression of chorioretinal atrophy (95.7% vs. 71.4%, P = 0.027) and less frequent photoreceptor recovery (17.4% vs. 65.3%, P < 0.001) after anti-VEGF therapy. Occurrence of subretinal fibrosis was associated with poor vision at baseline ( P = 0.011) and the final visit ( P = 0.008) when compared with the findings in the nonoccurrence group. Conclusion: Development of subretinal fibrosis after anti-VEGF therapy was common in eyes with myopic CNV and was associated with CNV recurrence. Myopic eyes with subretinal fibrosis show progressive chorioretinal atrophy and poor visual outcome. Abstract : Subretinal fibrosis occurs in approximately one third of eyes with myopic choroidal neovascularization (CNV) after antivascular endothelial growth factor therapy. Subretinal fibrosis leads to more frequent progression of chorioretinal atrophy, less frequent photoreceptor recovery, and poor visual outcomes. Choroidal neovascularization recurrence is associated with the development of subretinal fibrosis.